Association between age and serum ferritin level with bone age deficit in children with thalassemia major - Sri Hastuti Andayani; Nanan Sekarwana; Ryadi Fadil (Paediatrica Indonesiana, 2008)
Background Multiple blood transfusions in thalassemia patientslead to iron overload in bone tissue. Iron overload can bedetermined by serum ferritin measurement. Several studies haveevaluated association between serum ferritin level and growth,but without bone age examination.Objective To determine the association between age and serumferritin level with bone age in children with thalassemia major.Methods This study was conducted at Hasan Sadikin HospitalBandung during March-May 2007. We performed physicalexamination, serum feritin measurement, and bone ageexamination. Data were analyzed with x 2 to determine associationbetween variables. The association between age and serum ferritinlevel with bone age deficit was analyzed with regression logisticmodel.Results Subjects consisted of 49 patients with thalassemia major.All subjects had bone age deficit. Most boys were in age group of>10 years and had bone age difference >36 months, while mostgirls were <10 years and had bone age difference <36 months.Subjects with bone age difference <36 months mostly had serumferritin level <5,000 ng/dL, while most subjects with bone agedifference >36 months had serum ferritin level =5,000 ng/dL.This was statistically significant (x 2 =4.573, P=0.032). There wasassociation between age and bone age deficit (OR=13.461, 95%CI 3.199;56.640), but not with serum ferritin level (OR= 2.199,95% CI 0.532;9.095).Conclusion In thalassemic children, bone age deficit is associatedwith age, but not with serum feritin level.